Treatment effectiveness and outcome in patients with a relapse and newly diagnosed multidrug-resistant pulmonary tuberculosis - Dmytro Butov; Valeriy Myasoedov; Mykola Gumeniuk; Galyna Gumeniuk; Oleksandra Choporova; Anton Tkachenko; Oleksandra Akymenko; Olena Borysova; Olena Goptsii; Yevhenii Vorobiov; Tetiana Butova (Medicinski glasnik, 2020)
Aim: To investigate the treatment effectiveness and outcome in patients with pulmonary tuberculosis relapse and newly diagnosed multidrug resistant pulmonary tuberculosis (MDR-TB). Methods: A total of 240 pulmonary MDR-TB patients, including 114 ones with tuberculosis relapse and 126 cases of newly diagnosed pulmonary tuberculosis, were examined. Effectiveness of the basic antimycobacterial therapy course was evaluated based on the time to normalization of tuberculosis clinical manifestation, sputum culture and acid-fast bacilli stain conversion, cavity closure, disappearance of infiltrative and focal changes in the pulmonary tissue. Treatment outcomes were evaluated as cured, treatment completed, treatment failed, died and lost to follow-up according to the World Health Organization guidelines. Results: When assessing the treatment effectiveness in patients with MDR-TB, a worse clinical and chest radiograph dynamics was observed in tuberculosis relapse against the background of high parameters of treatment failure (18.4 %) and low cured (34.2 %) compared with newly diagnosed pulmonary tuberculosis (7.1% and 58.7 %, respectively) (p=0.008 and p<0.001, respectively). Conclusion: Standard treatment effectiveness in patients with newly diagnosed MDR-TB manifested by faster improvement and stabilization of health, earlier sputum culture and smear conversion, higher frequency of cavity closure and achievement of certain clinical and radiographic improvement against the background of fewer cases of treatment failure and a higher number of cured patients compared with MDR-TB relapse.
Keywords: Mycobacterium; X-ray; culture; microscopy Methods